Study on the growth factors and hepatoprotective effect of Beta vulgaris L. in male Wistar rats - Al Nouri, Doha Mustafa; Althalmawi, Hallah Oqalaa; Al Faifi, Latifa Yahiya; Owayedh, Hussah Mohammed Al; Arzoo, Shaista (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The purpose of this study was to investigate the effect of Beta vulgaris L. juice on growth and liver enzymes in male Wistar rats. The experiment was conducted on 15 Wistar albino rats, divided into 3 groups. Group 1 was fed with a standard diet (control group), group 2 was fed with a standard diet and 1 ml Beta vulgaris L. juice and group 3 was fed with a standard diet and 2 ml Beta vulgaris L. juice. Statistically insignificant difference was observed between control and experimental groups for total food consumption. Similarly difference was insignificant for final weight but it has been found that change in weight was slightly more in control group whencompared to experimental group fed with 2 ml juice although the change in weight was insignificant between control and experimental groups. It has been found that administration of Beta vulgaris L. decreased the AST and ALT activities in serum so it can be concluded from this study that beetroot feeding may protect against liver damage.